BACTERIAL CONJUNCTIVITIS OF ADULTS: CAUSES AND OPHTHALMIC ANTIBIOTIC RESISTANCE PATTERNS FOR THE COMMON BACTERIAL ISOLATES - Al-Eryani, Sameha A.; Alshamahi, Essam Yahya A; Al-Shamahy, Hassan A.; Alfalahi, Ghada Hussein A; Al-Rafiq, Abdulrahman Ahmed (Universal Journal of Pharmaceutical Research, 2021)
Background: Bacterial conjunctivitis is often observed in newborns as well as in other age groups. It has been associated with several organisms that differed in their relative importance and varied in their response to ophthalmic antibiotics. Objectives: The aim of this study was to investigate bacterial conjunctivitis of adult patients by determine the specific bacterial causes and determine the ophthalmic antibiotic resistance patterns for the bacterial isolates from conjunctivitis patients in Sana’a city, Yemen. Methods: Total 521 bacterial swabs obtained from adult patients with suspected bacterial conjunctivitis introducing to the ophthalmology clinics in the tertiary hospitals in Sana’a city, Yemen between September 2016 and October 2017 were investigated for bacteriological agents and antibiotic susceptibility . The clinical samples culturing, and microbiology diagnosis were done at National Center of Public Health laboratories Sana’a (NCPHL). Result: Total 521 swab results from conjunctiva were performed, of which 206 (39.5%) were deemed positive for bacterial culture. The isolation rate by bacteria species ranged from 0.5% to 28.2%. In Staphylococcus aureus isolates, ophthalmic antibiotic resistance varied from 10.5% for polymyxin B to 66.7% for erythromycin. In Branhamella catarrahalis isolates, ophthalmic antibiotic resistance ranged from 3.4% for levofloxacin to 69% for erythromycin. In Haemophilus influenzae isolates, ophthalmic antibiotic resistance varied from 0.0% for ciprofloxacin and polymyxin B to 42.1% for erythromycin and azithromycin. Conclusion: The most common causative organisms in adult age groups were Branhamella catarrahalis and Staphylococcus aureus. Obviously, there is no single drug that treats these various types of bacteria. Therefore, bacteriological culture and sensitivity in the laboratory to ophthalmic antibiotics should be performed as much as possible. But if laboratory facilities are not available, some generalizations can be made as guidelines for treating conjunctivitis. Peer Review History: Received 9 December 2020; Revised 5 January 2021; Accepted 13 February; Available online 15 March 2021 Academic Editor: Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Reviewer(s) detail: Dr. Bilge Ahsen KARA , Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. Gulam Mohammed Husain , National Research Institute of Unani Medicine for Skin Disorders, Hyderabad, India, gmhusain@gmail.com Dr. Mujde Eryilmaz , Ankara University,Turkey, meryilmaz@ankara.edu.tr